Improving Breast Cancer Family Caregivers' Palliative Care Literacy: A Pilot Randomized Trial. (February 2023) - Schulman-Green, Dena; Linsky, Sarah; Blatt, Leslie; Jeuland, Jane; Kapo, Jennifer; Jeon, Sangchoon
Self- and family management (SFM) refers to patients' and family caregivers' activities to co-manage illness. Two barriers to SFM are low palliative care literacy and lack of goals of care communication, which potentially result in SFM activities that are unsupportive of patients' goals. Managing Cancer Care: A Caregiver's Guide (MCC-CG) aims to improve palliative care literacy and communication within a SFM training program. In this pilot randomized trial, we enrolled breast cancer family caregivers and collected data at 0, 1, and 3 months on palliative care literacy, SFM engagement, communication, transitions management, uncertainty, caregiver burden, and caregiver competence/personal gain. Participants ( n = 35) had a mean age of 54 (range: 18–81) and were 66% white and 34% racial/ethnic minorities. Intervention participants improved their palliative care literacy and SFM engagement, reduced uncertainty and caregiver burden, increased competence/personal gain, and had more goals of care conversations over time. MCC-CG has preliminary efficacy, warranting further study.